Barriers and facilitators to maternal death surveillance and response at a busy urban National Referral Hospital in Uganda [version 2; peer review: 2 approved] - Jolly Beyeza-Kashesya; Dan K.Kaye; Joseph Rujumba; Noah Kiwanuka; Moses Mukuru; Imelda Namagembe; Annettee Nakimuli; Josaphat Byamugisha; Ashley Moffett (Open Research Africa, 2023)
Background: Preventable maternal and newborn deaths remain a global concern, particularly in low- and- middle-income countries (LMICs) Timely maternal death surveillance and response (MDSR) is a recommended strategy to account for such deaths through identifying contextual factors that contributed to the deaths to inform recommendations to implement in order to reduce future deaths. Implementation of MDSR is still suboptimal due to barriers such as inadequate skills and leadership to support MDSR. With the leadership of WHO and UNFPA, there is momentum to roll out MDSR, however, the barriers and enablers for implementation have received limited attention. These have  implications for successful implementation. The aim of this study was: To assess barriers and facilitators to implementation of MDSR at a busy urban National Referral Hospital as perceived by health workers, administrators, and other partners in Reproductive Health. Methods: Qualitative study using in-depth interviews (24), 4 focus-group discussions with health workers, 15 key-informant interviews with health sector managers and implementing partners in Reproductive-Health. We conducted thematic analysis drawing on the Theory of Planned Behaviour (TPB).   Results: The major barriers to implementation of MDSR were: inadequate knowledge and skills; fear of blame / litigation; failure to implement recommendations; burn out because of workload   and inadequate leadership- to support health workers. Major facilitators were involving all health workers in the MDSR process, eliminate blame, strengthen leadership, implement recommendations from MDSR and functionalize lower health facilities (especially Health Centre -IVs). Conclusions: The barriers of MDSR include knowledge and skills gaps, fear of blame and litigation, and other health system factors such as erratic emergency supplies, and leadership/governance challenges. Recommendation: Efforts to strengthen MDSR for impact should use health system responsiveness approach to address the barriers identified, constructive participation of health workers to harness the facilitators and addressing the required legal framework.